Updating the biological interest of 'Valeriana officinalis' - Sánchez, Marta; González-Burgos, Elena; Iglesias, Irene; Gómez-Serranillos Cuadrado, M. Pilar (Mediterranean Botany, 2021)
Valeriana officinalis L. (Caprifoliaceae) has been traditionally used to treat mild nervous tension and sleep problems. The basis of these activities are mainly attributed to valerenic acid through the modulation of the GABA receptor. Moreover, V. officinalis is claimed to have other biological activities such as cardiovascular benefits, anticancer, antimicrobial and spasmolytic. The current review aims to update the biological and pharmacological studies (in vitro, in vivo and clinical trials) of V. officinalis and its major secondary metabolites in order to guide future research. Databases PubMed, Science Direct and Scopus were used for literature search including original papers written in English and published between 2014 and 2020. There have been identified 33 articles which met inclusion criteria. Most of these works were performed with V. officinalis extracts and only a few papers (in vitro and in vivo studies) evaluated the activity of isolated compounds (valerenic acid and volvalerenal acid K). In vitro studies focused on studying antioxidant and neuroprotective activity. In vivo studies and clinical trials mainly investigated activities on the nervous system (anticonvulsant activity, antidepressant, cognitive problems, anxiety and sleep disorders). Just few studies were focused on other different activities, highlight effects on symptoms of premenstrual and postmenopausal syndromes. Valeriana officinalis continues to be one of the medicinal plants most used by today's society for its therapeutic properties and whose biological and pharmacological activities continue to arouse great scientific interest as evidenced in recent publications. This review shows scientific evidence on traditional uses of V. officinalis on nervous system.